Integration of an algorithmic BIM approach in a traditional architecture studio. Issue 3 (29th November 2018) - Caetano, Inês; Leitão, António
Graphical abstract: Abstract: Algorithmic BIM (A-BIM) is a design paradigm that merges the potentialities of both Algorithmic Design (AD) and Building Information Modelling (BIM). This paper describes how the A-BIM approach was integrated into the design workflow of two traditional design studios, to develop a set of parametric facades for a residential building, from which we automatically extracted material quantities and construction details. This work demonstrates how the combination of AD with BIM influenced the whole design process and the selection of the final solution. The limitations found during the entire process are also addressed, such as tight deadlines and financial constraints. Finally, the pros and cons of using an A-BIM process compared to a traditional BIM approach are discussed, as is the implementation of this paradigm in a traditional design practice. We also show how the efficiency of the A-BIM process can be greatly increased by the use of an Integrated Development Environment for AD supporting the generation of 3D models in both Computer-Aided Design (CAD) and BIM applications.